Endocytosis and Physiology: Insights from Disabled-2 Deficient Mice - Tao, Wensi; Moore, Robert; Smith, Elizabeth R.; Xu, Xiang-Xi (Frontiers in Cell and Developmental Biology, 2016)
ABSTRACT Disabled-2 (Dab2) is a clathrin and cargo binding endocytic adaptor protein, and cell biology studies revealed that Dab2 plays a role in cellular trafficking of a number of transmembrane receptors and signaling proteins. A PTB/PID domain located in the N-terminus of Dab2 binds the NPXY motif(s) present at the cytoplasmic tails of certain transmembrane proteins/receptors. The membrane receptors reported to bind directly to Dab2 include LDL receptor and its family members LRP1 and LRP2 (megalin), growth factor receptors EGFR and FGFR, and the cell adhesion receptor beta1 integrin. Dab2 also serves as an adaptor in signaling pathways. Particularly, Dab2 facilitates the endocytosis of the Ras activating Grb2/Sos1 signaling complex, controls its disassembly, and thereby regulates the Ras/MAPK signaling pathway. Cellular analyses have suggested several diverse functions for the widely expressed proteins, and Dab2 is also considered a tumor suppressor, as loss or reduced expression is found in several cancer types. Dab2 null mutant mice were generated and investigated to determine if the findings from cellular studies might be important and relevant in intact animals. Dab2 conditional knockout mice mediated through a Sox2-Cre transgene have no obvious developmental defects and have a normal life span despite that the Dab2 protein is essentially absent in the mutant mice. The conditional knockout mice were grossly normal, though more recent investigation of the Dab2-deficient mice revealed several phenotypes, which can be accounted for by several previously suggested mechanisms. The studies of mutant mice established that Dab2 plays multiple physiological roles through its endocytic functions and modulation of signal pathways.